PENGETAHUAN DAN KETERAMPILAN BIDAN DESA DALAM UPAYA PENINGKATAN KUALITAS PELAYANAN ANTENATAL CARE DI KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT - , Muhamad Zuhaeri, Prof. dr. Djaswadi Dasuki, MPH, SpOG(K), Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Various context and structure conditions in healthcare system will be affected the effectiveness of maternal and child health programs particularly antenatal care. More efforts have been done to improve those programs such as increasing knowledge and skills that have supported by the organization. Education and training programs is one of programs that were shown to improve the mastery of midwifery care competencies related to mastery of services standard based antenatal care competencies. Objectives: The purposes of this study were to evaluate the quality of clinical assessment knowledge and clinical assessment skills for the village midwives in antenatal care and organizational support which were education, supervision, and completeness of equipments. Methods: The design of this study was mixed methods approaches with cross-sectional study. Results: Univariable analysis indicated that 23.6% of village midwives didnât know about clinical assessment in antenatal care, 61.8% of village midwives didnât perform the clinical assessment in antenatal care practice, 60% of village midwives didnât obtain supervision, and 49.1% of village midwives had no completeness equipment of antenatal care. Bivariable analysis showed that there were significantly associations between knowledge with clinical assessment in antenatal care practice (p<0.05), whereas Multivariable analysis showed that the associations between education and supervision in knowledge of clinical assessment and clinical assessment in village midwives practice of antenatal care (deviance >0.231). Conclusion: There were significantly associations between assessment clinical knowledge and assessment clinical practice in antenatal care (p<0.05). Those were determined by village midwives education and supervision. Therefore, It should be improved the performance quality of village midwives in antenatal care, particularly through supporting education, training and supervision programs, accreditation, certification of midwives and equipment suport.